THE IMPLEMENTATION OF DRINKING WATER SUPPLY SYSTEM IN DECENTRALIZATION ERA - Hanim, Wasifah (TRIKONOMIKA, 2018)
This study aims to analyze the system of drinking water management in the decentralization era and to to analyze of the difference of community accessibility to drinking water between before and after the era of decentralization. The analytical method used is descriptive method, which is analyzing the implementation of drinking water supply systems (DWSS) in the decentralization era and average difference test to determine the development of community accessibility to drinking water before and after decentralization era. The result shows that decentralization provides a positive development towards the implementation of the drinking water supply system, namely by increasing the number of districts/cities that have DWSS planning documents but statistically the decentralization era did not increase the growth of drinking water coverage.